An overview of Greenland's mineral exploration potential - Schønwandt, H.K; Dawes, P.R (Rapport Grønlands Geologiske Undersøgelse, 1993)
Part of the 1992 promotion campaign to North America and Europe, to provide geoscientific data to exploration and mining audiences was an oral presentation of Greenland's exploration potential. The background and aims of the campaign are outlined elsewhere in this report by Dawes et al. The oral presentation focused on the main geological provinces of Greenland and their mineral occurrences (excIuding fossil fuels), but geographical and logistic subjects were also broached. This paper gives a summary of the geological part of the presentation and concentrates on metalliferous potential.